The craft beer market in Argentina: An exploratory study of local brewers' and consumers' perceptions in Mar del Plata - Belmartino, Andrea (2020)
During the last twenty years, Argentina's craft beer industry has experienced steady growth, which led to an increase in the number of both breweries and consumers. One of the first and most important craft beer clusters in the country is in Mar del Plata, a popular tourist destination on the coast in east-central Argentina. The sustained popularity of craft beer in this city provides an interesting case study to analyze thoroughly the evolution of a craft beer cluster in a developing country. This article aims to analyze producers' perceptions as well as consumers' preferences toward craft beer, in order to understand the craft beer drinkers’ decisions and choices. We interviewed five craft brewers and conducted two focus groups with local craft beer consumers. The results show that neolocalism is highly valued in the industry by both producers and consumers. We identify two groups of craft beer consumers: beginners or social consumers and sophisticated or craft beer lovers. The attributes most appreciated by consumers are quality, flavor, and bitterness.